1990
DOI: 10.1530/jrf.0.0900625
|View full text |Cite
|
Sign up to set email alerts
|

Control of endometrial oxytocin receptor and uterine response to oxytocin by progesterone and oestradiol in the ewe

Abstract: The effects of administration of progesterone and oestradiol on ovine endometrial oxytocin receptor concentrations and plasma concentrations of 13,14-dihydro-15-keto prostaglandin F-2 alpha (PGFM) after oxytocin treatment were determined in ovariectomized ewes. Ewes received progestagen pre-treatment, progesterone and/or oestradiol in 11 different treatment schedules. Progestagen pre-treatment decreased oxytocin receptor concentrations in endometrium from ewes treated subsequently with either progesterone for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
77
1
13

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 21 publications
11
77
1
13
Order By: Relevance
“…Progesterone may act on the hypothalamic-pituitary pathway (Martin et al, 1983), or at the level of the ovary (Hunter et al, 1986;Brown et al, 1988) or uterus. This latter suggestion has been widely studied (Vallet et al, 1990).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Progesterone may act on the hypothalamic-pituitary pathway (Martin et al, 1983), or at the level of the ovary (Hunter et al, 1986;Brown et al, 1988) or uterus. This latter suggestion has been widely studied (Vallet et al, 1990).…”
Section: Introductionmentioning
confidence: 87%
“…However, this is unlikely as when one administers intramuscularly 20 mg progesterone to hysterectomized ewes, the elimination of the hormone is slower (4 days, fig 3c) than in intact ewes (1 day, Lassoued et al, 1995 (Hunter et al, 1989). Progestagen treatment inhibits the establishment of oxytocin receptors and the release of prostaglandins in response to oxytocin administration (Vallet et al, 1990 (Rubianes et al, 1996) and probably reduces the increase in E2 secretion observed by Mattner and Braden (1972).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There may also be important variations within specific oxytocin synthesizing cells, with subpopulations of parvocellular and magnocellular neurones responding with different sensitivities. It is also likely that steroids influence post-receptor transduction events (Vallet et al, 1990). Certainly the results listed above provide compelling evidence that receptors in different brain areas respond differentially to gonadal steroids.…”
Section: Regulation Of Oxytocin Receptors In the Brainmentioning
confidence: 96%
“…En effet, ce nonapeptide peut aussi être synthétisé, stocké et libéré par le corps jaune (Wathes et Swann, 1982 ;Flint et Sheldrick, 1982 ;Watkins, 1983 ;Rodgers et al, 1983 ;Swann et al, 1984) et c'est ainsi que les augmentations de pression intramammaires observées dans cette espèce, après injection intrajugulaire de PGF2a (Labussière ef al, 1983), résul-tent probablement de l'action de cette hormone lutéale puisque les réponses sont abolies après castration (Labussière et al, 1986), lutectomie (Labussière et al, 1990) ou interruption de la circulation sanguine dans la vascularisation ovarienne (Labussière et Combaud, 1989 (Lakshmanan et al, 1958 ;Elliot, 1959 ;Linzell et Peaker, 1971 ;Labussière et al, 1978). (Nissenson et al, 1978 ;Soloff et al, 1983), il faut malgré tout signaler qu'un pré-traitement à l'acé-tate de fluorogestone suivi d'un traitement progestéronique peut conduire à des résul-tats inverses (Vallet et al, 1990) et il faut aussi savoir que les récepteurs à l'ocytocine de l'utérus et de la mamelle ne semblent pas être soumis au même type de régulation (Soloff et al, 1979 ;Soloff, 1982 Il apparaît donc souhaitable de poursuivre ces travaux sur l'effet galactopoïéti-que des corps jaunes multiples en cherchant à dissocier l'importance relative de l'ocytocinémie (qui facilite le transfert du lait alvéolaire dans la citerne) et de la progestéronémie qui pourrait intervenir non seulement sur le métabolisme des cellules sécrétrices mammaires mais aussi sur la réceptivité à l'ocytocine des cellules myoé-pithéliales.…”
unclassified